Growth of Trichoderma asperellum with the Addition of Glycerol on Rice Bran Based Medium - Chahyunisa, Alifia; Anhar, Azwir (Jurnal Serambi Biologi, 2024)
Biofertilizer is a material that contains live microorganisms that are able to increase plant nutrition, one of which is Trichoderma. Trichoderma is able to have a positive influence on plants, plant growth and plant production results. Bran is a material that can be used as a growth medium for Trichoderma sp because it is able to increase nutrition in plants and is able to meet the needs needed for the growth and development of Trichoderma. The shelf life of bran is limited, therefore glycerol is added to the bran medium. This research is an experimental study using a Completely Randomized Design (CRD) with 6 treatments and 5 replications. The research was carried out by making a Trichoderma asperellum formulation using bran as the basic ingredient and adding glycerol at concentrations namely 0%, 20%, 40%, 60%, 80% and 100%. Data in the form of the number of spores at each concentration were analyzed using analysis of variance. The results of the research showed that for Trichoderma asperellum, giving different concentrations of glycerol in bran-based media did not affect the number of Trichoderma asperellum spores and shelf life because there was no real difference between the different concentrations given.